2021
DOI: 10.1177/10436596211061683
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Academic Self-Efficacy Among Nursing Students During COVID-19: A Path Analysis

Abstract: Introduction: The shift to online learning owing to the coronavirus disease 2019 pandemic is posing an additional challenge to academic success, particularly for students who speak English as a Second Language (ESL). This study aimed to examine the factors that contribute to academic self-efficacy among ESL nursing students. Method: This was a cross-sectional study using path analysis with 113 undergraduate ESL nursing students in New York City. Data were collected online using self-report measures of the stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Anxiety has been shown to increase susceptibility to pressure at work and to have a negative impact on self-efficacy, as it reduces positive behaviours and initiative [ 62 , 63 , 64 ]. In their study, Han et al revealed that stress caused by e-learning has a negative impact on self-efficacy in members of the academic community [ 65 ]. Earlier studies showed that the COVID-19 pandemic had had a negative impact on self-efficacy, and a majority of students in the online teaching regime had experienced negative emotions, including anxiety and stress [ 66 , 67 , 68 , 69 , 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Anxiety has been shown to increase susceptibility to pressure at work and to have a negative impact on self-efficacy, as it reduces positive behaviours and initiative [ 62 , 63 , 64 ]. In their study, Han et al revealed that stress caused by e-learning has a negative impact on self-efficacy in members of the academic community [ 65 ]. Earlier studies showed that the COVID-19 pandemic had had a negative impact on self-efficacy, and a majority of students in the online teaching regime had experienced negative emotions, including anxiety and stress [ 66 , 67 , 68 , 69 , 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Findings of study showed that 32.3% of the students had mild anxiety, 40.5% had moderate anxiety, 22.5% had high anxiety, and 4.7% had severe anxiety during the COVID-19 pandemic. [10][11][12][13] This study is similar to the present study as it had subjects with mild, moderate and severe anxiety.…”
Section: Discussionmentioning
confidence: 91%
“…However, it was lower than the academic self-efficacy of nursing students before the COVID-19 outbreak in China(3.53 ± 0.45) [ 32 ]. Previous studies also measured high levels of academic self-efficacy among nursing students in both the United States and Israel during the epidemic period [ 33 , 34 ]. Nevertheless, it is difficult to compare other national studies’ results with the results of this study because of the different measurement tools used.…”
Section: Discussionmentioning
confidence: 99%